Analisis Model Komunikasi Dakwah yang Efektif dalam Kehidupan Sehari-hari - Riska Amelia Putri; Mutifatul Hamdiyah; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Da'wah is a process of conveying Islamic teachings that is not limited to formal religious forums, but also occurs naturally in everyday life. The models studied include one-way, two-way, interpersonal, and persuasive communication. Each model has its own characteristics, advantages, and challenges in conveying Islamic messages effectively. One-way communication is suitable for lectures and sermons, but does not open up space for dialogue. In contrast, two-way communication is more inclusive and allows for the expansion and exchange of ideas. Interpersonal communication is effective in intimate relationships such as in families, while persuasive communication is able to touch emotions and attitudes without coercion. The application of these models in pluralistic societies, nuclear families, and the world of short-density work, communication skills, and the role models of da'wah practitioners. Successful da'wah does not only rely on words, but is also manifested through real behavior and high social awareness. Thus, every Muslim has a strategic role in spreading Islamic values ​​through appropriate communication models, full of wisdom, and compassion as exemplified by the Prophet Muhammad SAW.